Film-shaped adhesive, laminated lens provided with a cured film of the film-shaped adhesive, concentrated solution for film-shaped adhesive

CN123022769APending Publication Date: 2026-10-30FURUKAWA ELECTRIC CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580023078.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2025-03-26
Publication Date
2026-10-30

AI Technical Summary

Benefits of technology

[0041]根据本发明,能够抑制膜状粘合剂固化后的固化膜中的光的透射和反射。另外,膜状粘合剂的贴合性优异,而且在固化膜中能够发挥低吸水率和高温下的高粘合力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123022769A_ABST
    Figure CN123022769A_ABST
Patent Text Reader

Abstract

The present invention is to provide a film-shaped adhesive which has low light transmittance and reflectance when cured into a cured film. In addition, it is to provide a film-shaped adhesive which can satisfy adhesiveness before curing, low water absorption in a cured state, and adhesive force at high temperature at the same time, a laminated lens having a cured film of the film-shaped adhesive, and a concentrated solution for film-shaped adhesive. The solution is a film-shaped adhesive containing an epoxy resin (A), an epoxy resin curing agent (B), a high molecular component (C) containing a phenoxy resin, an inorganic filler (D), and a colorant (E), the film-shaped adhesive containing the inorganic filler (D) in a specific amount, the epoxy resin (A) in a specific amount, the epoxy resin curing agent (B) in a specific amount, and the colorant (E) in a specific amount.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a film adhesive, a laminated lens having a cured film of the film adhesive, and a concentrated solution of the film adhesive. Background Technology

[0002] Film-like adhesives are suitable for various industrial applications. For example, they are used for bonding various components in various electronic devices. For instance, in wafer-level lenses used in cameras and camcorders of portable devices, film-like adhesives are used for bonding and fixing the individual lenses when they are stacked to form lenses. Alternatively, adhesive sheets with a substrate containing a light-shielding adhesive layer are used to prevent light leakage from light sources such as backlight modules of liquid crystal display devices and self-emissive elements such as organic EL (electroluminescence) sensors, and to prevent reflections. Specifically, Patent Document 1 discloses an adhesive composition using a terpene phenol resin as the adhesive resin, an isocyanate crosslinking agent as the crosslinking agent, and carbon black in an acrylic adhesive polymer. The adhesive strength, shear adhesion, and shielding properties of this adhesive composition were evaluated under conditions of room temperature and a 180° peel angle. Patent Document 2 discloses an adhesive composition in which benzotriazole, terpene phenol resin, isocyanate crosslinking agent, epoxy crosslinking agent, etc., are incorporated into an acrylic polymer, and carbon black particles are used as a light-shielding material. The total light transmittance of the adhesive composition and its peel strength at room temperature and 180° were evaluated.

[0003] Existing technical documents

[0004] Patent documents

[0005] Patent Document 1: Japanese Patent No. 6945090 Specification

[0006] Patent Document 2: Japanese Patent Application Publication No. 2023-112140 Summary of the Invention

[0007] The problem the invention aims to solve

[0008] Figure 1This is a schematic cross-sectional view illustrating the structure of the stacked lens. The stacked lens 10 of this embodiment employs a structure in which three lenses 1 are stacked on top of the image sensor 2. A curing film 3 using a film-like adhesive is used to fix the three lenses 1, 1, 1 to their respective positions. Conventionally, colorless film-like adhesives have been used for the stacked lenses; however, this results in light intruding through portions of the film-like adhesive. Furthermore, light radiating from the inside out is not absorbed by the film-like adhesive but is reflected. This transmission and reflection of light causes halos and ghosting in the image during imaging. Additionally, the adhesion between the film-like adhesive and the lens, and the adhesive strength at high temperatures during the curing process, have not been adequately addressed until now, and products with superior properties cannot be considered.

[0009] Therefore, the object of the present invention is to provide a film-like adhesive with low light transmittance and reflectance when the cured film is formed. Furthermore, the object is to provide a film-like adhesive that exhibits excellent adhesion before curing and satisfies low water absorption and high adhesion at high temperatures in the cured state, a laminated lens having the cured film-like adhesive, and a concentrated liquid (slurry) for the film-like adhesive.

[0010] Solution for solving the problem

[0011] After repeated and in-depth research into the aforementioned technical problems, the inventors discovered that by using a film-like adhesive composed of a curable resin composition and setting the proportions of each component to specific amounts, multiple problems can be solved at once. The curable resin composition contains a polymer component (phenoxy resin) as the main agent, and further contains epoxy resin and its curing agent, inorganic filler, and colorant. That is, the present invention has the following solution.

[0012] (1) A film-like adhesive comprising epoxy resin (A), epoxy resin curing agent (B), polymer component (C), inorganic filler (D), and colorant (E), wherein,

[0013] The polymer component (C) includes phenoxy resin.

[0014] Relative to 100 parts by weight of the polymer component (C), the inorganic filler material (D) is 70 to 720 parts by weight.

[0015] Relative to 100 parts by weight of the polymer component (C), the epoxy resin (A) is 70 to 350 parts by weight.

[0016] The amount of epoxy resin curing agent (B) is 1.4 parts by weight or more, relative to 100 parts by weight of epoxy resin (A).

[0017] When the total amount of the epoxy resin (A) and the polymer component (C) is set to 100 parts by mass, the colorant (E) is 10 parts by mass or more.

[0018] (2) The film adhesive according to (1), wherein,

[0019] The light transmittance of the cured film after curing at 120℃~180℃ is less than 10% in the range of 400nm~1100nm when the thickness is 10μm~125μm.

[0020] (3) The film adhesive according to (1) or (2), wherein,

[0021] The cured film cured at 120℃~180℃ has a light reflectance of less than 7% in the range of 400nm~1100nm when the thickness is 10μm~125μm.

[0022] (4) The film adhesive according to any one of (1) to (3), wherein,

[0023] The thickness is in the range of 5μm to 150μm.

[0024] (5) The film adhesive according to any one of (1) to (4), wherein,

[0025] When heated from 25°C at a rate of 5°C / min, the melt viscosity at 70°C is in the range of 6,000~65,000 Pa·s.

[0026] (6) The film adhesive according to any one of (1) to (5), wherein,

[0027] The colorant (E) contains carbon black.

[0028] (7) The film adhesive according to any one of (1) to (6), wherein,

[0029] The phenoxy resin is a thermoplastic resin with a molecular weight of 10,000 to 100,000, obtained by reacting a bisphenol compound with a glycidyl group-containing compound.

[0030] (8) The film adhesive according to any one of (1) to (7), wherein,

[0031] The film adhesive is used for bonding lenses used in stacked lenses.

[0032] (9) A stacked lens, wherein...

[0033] In the bonding of the lens, the film adhesive described in any one of (1) to (8) is used, and the cured film of the film adhesive is assembled into the stacked lens in such a way that it is bonded at the bonding part.

[0034] (10) A concentrated solution for a film-like adhesive, characterized in that the solvent contains:

[0035] Phenoxy resin (C');

[0036] Epoxy resin (A) is 70 to 350 parts by weight relative to 100 parts by weight of phenoxy resin (C');

[0037] The epoxy resin curing agent (B) is 1.4 parts by mass or more relative to 100 parts by mass of epoxy resin (A);

[0038] Inorganic filler (D), comprising 70-720 parts by weight relative to 100 parts by weight of phenoxy resin (C'); and

[0039] The colorant (E) is 10 parts by mass or more when the total amount of the epoxy resin (A) and the phenoxy resin (C') is 100 parts by mass.

[0040] Invention Effects

[0041] According to the present invention, the transmission and reflection of light in the cured film after the film adhesive has cured can be suppressed. In addition, the film adhesive has excellent adhesion and can exhibit low water absorption and high adhesion at high temperatures in the cured film. Attached Figure Description

[0042] Figure 1 This is a cross-sectional view schematically illustrating one embodiment of the structure of a stacked lens.

[0043] Figure 2 This is a process illustration diagram showing the preparation and application process of the film adhesive of this embodiment. Detailed Implementation

[0044] The film adhesive of the present invention contains epoxy resin (A), epoxy resin curing agent (B), polymer component (C), inorganic filler material (D), and colorant (E). Hereinafter, preferred embodiments will be described in order of the above components.

[0045] <Epoxy Resin (A)>

[0046] Epoxy resins are used in this product and can be appropriately selected from curing resins. Examples include cycloalkane-containing epoxy resins, phenolic epoxy resins, and bisphenol-type epoxy resins. The bisphenol can be bisphenol A or bisphenol F, more preferably bisphenol A epoxy resin. Examples of epoxy resins include those having the following structure. n is a natural number, preferably 1 to 10, more preferably 1 to 4, and particularly preferably 1 to 2.

[0047]

Chemical Formula 1

[0048]

[0049] By adding epoxy resin and inorganic filler to the film adhesive of the present invention, adhesion strength and adhesion reliability can be ensured. Furthermore, thermosetting can be achieved by adding an epoxy resin curing agent.

[0050] The amount of epoxy resin used should preferably be adjusted to a suitable range, taking into account the combination with other additives such as curing agents. Specifically, relative to 100 parts by weight of the polymer component (C) described later, the amount of epoxy resin (A) is 70 parts by weight or more, preferably 90 parts by weight or more, and more preferably 100 parts by weight or more. The upper limit is 350 parts by weight or less, preferably 300 parts by weight or less, and more preferably 270 parts by weight or less. One or more types of epoxy resin can be used. When two or more types are used, their total amount is within the above-mentioned range.

[0051] The molecular weight of the epoxy resin (A) is not particularly limited, but is preferably 2,000 or less, more preferably 1,500 or less, and even more preferably 1,000 or less. The lower limit is not particularly limited, but 300 or more is practical.

[0052] <Epoxy Resin Curing Agent (B)>

[0053] The epoxy resin curing agent is preferably a compound capable of effectively curing the aforementioned epoxy resin. Curing of the epoxy resin can be either photocuring or heat curing; heat curing is preferred in this invention. Examples of epoxy resin curing agents include organic amine curing agents and imidazole curing agents (imidazole-cyano, imidazole-hydroxymethyl). Examples of epoxy resin curing agents include those having the following structures.

[0054] [Chemical Formula 2]

[0055] (CH3O)3SiC3H6NHC2H4NH2 (d)

[0056] [Chemical Formula 2]

[0057]

[0058]

Chemical Formula 3

[0059]

[0060] The amount of epoxy resin curing agent (B) can be appropriately selected based on the amount of epoxy resin (A). Relative to 100 parts by weight of epoxy resin (A), the amount of epoxy resin curing agent (B) should be 1.4 parts by weight or more, preferably 1.8 parts by weight or more, and more preferably 2 parts by weight or more. Although there is no specific upper limit, considering the blooming effect of the resin components, it is not advisable to use too much; preferably 30 parts by weight or less, more preferably 20% by weight or less, and even more preferably 10 parts by weight or less. One or more epoxy resin curing agents can be used. When two or more components are included, their total amount is specified.

[0061] <Polymer Component (C)>

[0062] In this invention, the polymer component uses phenoxy resin. Phenoxy resin is preferably an amorphous thermoplastic resin that has undergone molecular weight refining of bisphenol compounds (bisphenol A, bisphenol F, etc.) and low molecular weight compounds containing glycidyl groups (epimchlorohydrin, etc.). Here, low molecular weight refers to compounds with a molecular weight less than 500.

[0063] When a structural formula is shown as an example of a phenoxy resin, the following examples can be cited. In the formula, n is a natural number, preferably 30 to 300, more preferably 45 to 250, and even more preferably 60 to 200. * in the formula represents a bonding end.

[0064] [Chemical Formula 4]

[0065]

[0066] By using phenoxy resin in the film adhesive of the present invention, higher adhesive strength than that of acrylic resin can be ensured. Furthermore, the use of phenoxy resin optimizes film properties (handling).

[0067] Phenoxy resins are amorphous by increasing the repeating units of the polymer, and are preferably thermoplastic resins. Using phenoxy resins as a polymeric component ensures high adhesive strength. Furthermore, using phenoxy resins ensures film-forming properties (handling). The amount of polymeric component (C) can be determined considering the shape stability of the uncured (semi-cured) film adhesive. The amount of polymeric component (C) can be determined by its relationship with other components.

[0068] The molecular weight of the polymer component (C) is not particularly limited, but is preferably 10,000 or more, more preferably 15,000 or more, and even more preferably 20,000 or more, based on weight-average molecular weight. The upper limit is preferably 100,000 or less, more preferably 80,000 or less, and even more preferably 75,000 or less.

[0069] In this invention, unless otherwise stated, "molecular weight" refers to the weight-average molecular weight of polystyrene as determined by gel permeation chromatography (GPC). The support may be suitably selected, for example, THF (tetrahydrofuran).

[0070] <Inorganic Filler Materials (D)>

[0071] Inorganic filler materials can be selected and appropriately used from those used in this product. Examples include silicon compounds, silicic acid, calcium silicate, silica gel, glass fiber, and vinyl silane-treated silica. Besides silicon compounds, other examples include calcium carbonate, molybdenum oxide, barium sulfate, carbon fiber, various ferrites, alumina, aluminum nitride (AlN), BN, BeO, mica, graphite, iron powder, lead powder, talc, titanium oxide, antimony oxide, aluminum hydroxide, magnesium hydroxide, and zinc oxide. In this invention, silicon compounds are preferred, and vinyl silane-treated silica is particularly preferred.

[0072] Regarding the amount of inorganic filler material, considering its effects and disadvantages, it is preferable to adjust it to a suitable range before use. Specifically, relative to 100 parts by mass of the polymer component (C), the amount of inorganic filler material (D) is 70 parts by mass or more, preferably 100 parts by mass or more, and more preferably 130 parts by mass or more. The upper limit is 720 parts by mass or less, preferably 650 parts by mass or less, and more preferably 500 parts by mass or less. When the inorganic filler material contains two or more components, their combined amount is specified.

[0073] <Colorant (E)>

[0074] Colorants are important in determining the optical properties of film adhesives. Specifically, they preferably have low light transmittance and low light reflectance. From this point of view, black colorants are preferred, and carbon black is more preferred. By adding a colorant (such as carbon black) to the film, light transmittance and reflectance can be suppressed.

[0075] When the total amount of the epoxy resin (A) and the polymer component (C) is set to 100 parts by mass, the colorant (E) is 10 parts by mass or more, preferably 12 parts by mass or more, and more preferably 14 parts by mass or more. Although there is no specific upper limit, considering issues such as blooming, it is not advisable to use too much, so it is preferably 50 parts by mass or less, more preferably 45 parts by mass or less, and even more preferably 40 parts by mass or less. When the colorant contains two or more components, their total amount is specified.

[0076] Solvent

[0077] The solvent used in manufacturing the film adhesive of the present invention is not particularly limited, and examples include alcohols, ketones, ethers, aryl hydrocarbons, aldehydes, esters, etc. Among them, ketones are preferred in the present invention, and MEK (methyl ethyl ketone) is more preferred. The amount of solvent used is preferably an amount that dissolves and disperses the above-mentioned compounding components and mixes them thoroughly, and on the other hand, it is preferable to use an amount that can evaporate during manufacturing and shape the film.

[0078] <Methods for manufacturing and applying film adhesives>

[0079] Figure 2 This is a process illustration diagram showing the preparation and application process of the film-like adhesive according to this embodiment. The film-like adhesive of this embodiment is prepared as follows: First, epoxy resin (A), epoxy resin curing agent (B), polymer component (C), inorganic filler (D), and colorant (E) are dissolved and dispersed in a solvent to prepare a concentrated film-like adhesive molding solution (dope). This concentrated film-like adhesive molding solution is then poured into a specified mold as needed, and the solvent is removed and shaped at a specified temperature. The temperature at this time is not particularly limited, but is preferably 70°C to 130°C (preferably 80°C to 120°C). The heating time is preferably 1 minute or more, more preferably 3 minutes or more, and even more preferably 5 minutes or more. Although there is no specific upper limit, 10 minutes or less is practical. The film-like adhesive in this state does not undergo a curing reaction caused by the internal epoxy groups and can be referred to as a semi-cured state. The shaped film-like adhesive can be used directly or shaped into the desired form by laser processing or the like. The formed film-like adhesive is cured at a temperature of 100°C to 210°C (preferably 120°C to 180°C), where the epoxy groups of the epoxy resin react with the epoxy resin curing agent to form an irreversibly cured film. The heating time is preferably 30 minutes or more, more preferably 1 hour or more, and even more preferably 2 hours or more. While there is no specific upper limit, 5 hours or less is practical.

[0080] <Manufacturing Method of Stacked Lenses>

[0081] Figure 1This is a cross-sectional view of an apparatus schematically illustrating one embodiment of the structure of a stacked lens. A pre-cured film adhesive is applied to at least a portion of the adhesive portion 12 of the stacked lens 1 for bonding, preferably by cutting to form sidewalls 11. In this embodiment, the lens 1 is stacked in three layers. A film adhesive is applied to the adhesive portion of each lens to form sidewalls 11. In this state, by exposing the semiconductor element to a high temperature (e.g., 150°C), the epoxy resin and epoxy resin curing agent, as described above, react to form a fully cured film 3. This fixes the shape, and cutting is performed as needed to manufacture a durable and high-strength stacked lens 10. Furthermore, in this embodiment, the product before cutting is called a wafer-level lens (wafer-level optical component), and the product after being monolithized by cutting is called a stacked lens (lens stack).

[0082] The shape of the stacked lenses is not particularly limited. To obtain the focal length, the spacer between the image sensor and the lens is preferably about 125 μm thick. For bonding between lenses, the spacer between lenses is preferably about 10 μm thick. Even when using a paste resin to make the spacer, it is difficult to produce a spacer with a thickness of more than 100 μm. This is achieved well by using the film-like adhesive of the present invention, which combines the functions of both bonding and spacer. From this perspective, the thickness of the film-like adhesive of the present invention is preferably 4 μm or more, more preferably 5 μm or more, and even more preferably 7 μm or more. The upper limit is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 130 μm or less. Furthermore, the film-like adhesive of this embodiment does not shrink or expand substantially when cured into a cured film, thus maintaining its shape. Therefore, the above-mentioned preferred thickness range also applies to the cured film.

[0083] Properties of film adhesives and cured films

[0084] The film-like adhesive of the present invention is in a pre-cured state. When it is formally cured (100~210°C, preferably 120~180°C, more preferably 180°C) and becomes a cured film, it is preferably 10 μm to 125 μm thick and has a light transmittance of less than 10% in the range of 400 nm to 1100 nm, more preferably less than 8%, and even more preferably less than 5%. Although there is no specific lower limit value, it is preferably completely opaque.

[0085] Regarding reflectivity, when formally cured (100°C to 210°C, preferably 120°C to 180°C, functionally preferably 180°C) and becomes a cured film, it is preferable that the thickness is 10 μm to 125 μm and the reflectivity is less than 15% in the range of 400 nm to 1100 nm, more preferably less than 10%, and even more preferably less than 7%. Although there is no specific lower limit value, it is preferable that there is no reflection of light at all.

[0086] Furthermore, by suppressing the light transmittance and reflectance specified here, ghosting and halos during imaging can be suppressed. A halo refers to the phenomenon of light leaking into the dark areas of a photograph, caused by the reflection of strong light from the camera and lens. Ghosting refers to the phenomenon where reflected light from a lens appears in a spherical or banded shape.

[0087] The adhesive film of the present invention, in its cured film state after formal curing, preferably exhibits an adhesive strength of 5 MPa or more at 260°C, more preferably 6 MPa or more, and even more preferably 7 MPa or more. While there is no specific upper limit, 25 MPa or less is practical. Furthermore, the films in Patent Documents 1 and 2 are designed for peelability, resulting in weaker adhesive strength. Additionally, heating to 260°C is not a prerequisite; even if intentionally heated to 260°C, the viscosity would decrease excessively, making it impossible to maintain morphological stability.

[0088] When the film adhesive of the present invention is heated from 25°C at a heating rate of 5°C / min, the melt viscosity at 70°C is preferably in the range of 6,000 to 65,000 Pa·s, more preferably in the range of 8,000 to 50,000 Pa·s, even more preferably in the range of 10,000 to 40,000 Pa·s, and particularly preferably in the range of 12,000 to 35,000 Pa·s.

[0089] The water absorption rate of the film adhesive of the present invention is preferably 2% or less, more preferably 1.5% or less, even more preferably less than 1.3%, particularly preferably 1.2% or less, and even more preferably 1.1% or less. There is no particular limitation on the lower limit, but 0.3% or more is practical.

[0090] Up to this point, the embodiments of the present invention have been described primarily in terms of their application in stacked lenses. However, the film adhesive of the present invention is not limited to this application, and can also be used as a sealing material for light sources such as backlight modules of liquid crystal display devices, a sealing material for self-emissive elements such as organic EL, and for automotive LiDAR, etc.

[0091] Example

[0092] <Combined Ingredients>

[0093] [Epoxy Resin (A)]

[0094] RE-310S

[0095] Bisphenol A type epoxy resin (manufactured by Nippon Kayaku Co., Ltd.)

[0096] ZX-1059

[0097] Liquid BPA / BPF type high-purity epoxy resin (manufactured by Nippon Steel Chemicals & Materials Co., Ltd.)

[0098] XD-1000

[0099] Manufactured by Nippon Kayaku Co., Ltd., with a weight-average molecular weight of 1,200.

[0100] [Chemical Formula 5]

[0101]

[0102] LX1

[0103] Bisphenol A type epoxy resin. Manufactured by Daisō Chemical Co., Ltd.

[0104] JER1002

[0105] Bisphenol A type epoxy resin is produced by the condensation reaction of bisphenol A and epichlorohydrin. Manufactured by Mitsubishi Chemical Corporation.

[0106]

Chemical Formula 6

[0107]

[0108] EOCN-102 is a phenolic varnish-type epoxy resin.

[0109] [Chemical Formula 7]

[0110]

[0111] Manufactured by Nippon Kayaku Co., Ltd.

[0112] [Epoxy Resin Curing Agent (B)]

[0113] 2PHZ-PW

[0114] 2-Phenylacetyl-4,5-Dihydroxymethylimidazolium (manufactured by Shikoku Chemical Industry Co., Ltd.)

[0115] [Chemical Formula 8]

[0116]

[0117] 2PZ-CN

[0118] [Chemical Formula 9]

[0119]

[0120] DICY15 is a powdered dicyandiamide manufactured by Mitsubishi Chemical Corporation.

[0121] [Polymer component (C)]

[0122] YP50-EK35: Phenoxy resin, manufactured by Nippon Steel Chemicals & Materials Co., Ltd., with a weight-average molecular weight of 57,000.

[0123] SG-P3: An acrylate polymer with epoxy functional groups, manufactured by Nagase ChemteX Co., Ltd.

[0124] Weight average molecular weight: 850,000.

[0125] [Inorganic filler material (D)]

[0126] SC2050-MNU

[0127] MEK slurry for treating silica with vinylsilane (manufactured by Admatechs).

[0128] SC5050-MLC

[0129] Admafine SO-C5 MEK slurry

[0130] RY-200

[0131] Dimethylpolysiloxane treatment of silica

[0132] K180SV-CM2

[0133] MEK slurry for treating silica with vinyltrimethoxysilane

[0134] [Coloring agent (E)]

[0135] ♯30L Carbon Black

[0136] A903 Carbon Black

[0137] ET6N109

[0138] 50-60% by weight of bisphenol A type epoxy resin

[0139] Carbon black 15~25% by mass

[0140] <Example 1>

[0141] (Preparation of concentrated solutions for film adhesives)

[0142] Weigh out 50 parts by weight of the above-mentioned RE-310S, 20 parts by weight of the above-mentioned JER1002, 1 part by weight of 2PHZ-PW, 100 parts by weight of YP50-EK35, 200 parts by weight of SC2050-MNU, and 25 parts by weight of A903 and mix them. Stir in a sufficient amount of MEK (methyl ethyl ketone) for one hour to dissolve and disperse these components. Thus, the concentrated liquid (slurry) s1 of Example 1 was prepared.

[0143] (Preparation of film adhesives: pre-curing)

[0144] The concentrated liquid s1 was poured into a mold of a specified thickness and left to stand in a constant temperature chamber at 110°C for 3 minutes to remove the solvent, thereby obtaining the morphologically stable film-like adhesive s1 of Example 1. The size was 10mm × 10mm. Furthermore, a release liner was pre-laid in the mold.

[0145] (Cure of film adhesives: formal curing)

[0146] The obtained film-like adhesive s1 with release diaphragms is processed into the desired shape using laser processing. This is then bonded to a virtual silicon wafer serving as an image sensor. The release diaphragms are then removed. Furthermore, the virtual silicon wafer serving as a lens is bonded using the film-like adhesive s1. This step is repeated to obtain a silicon wafer stack with three substrate layers. Next, it is heat-treated at 180°C for 1 hour to obtain a wafer stack s1 with the cured film s1 sandwiched between layers (the first layer of film-like adhesive has a thickness of 125 μm, and the other film-like adhesives have a thickness of 10 μm). This stack is then cut to obtain a simulated image sensor. Figure 1 The virtual silicon wafer structure s1 of the monolithic lens shown is illustrated.

[0147] <Example 2 and subsequent examples>

[0148] Example 2 and subsequent examples were prepared in the same manner as in Example 1, except that the formulation and the thickness of the film adhesive were changed as shown in Tables 1, 2, and 3. In each example, the temperature and time for curing the film adhesive (formal curing) were set to 180°C and 1 hour.

[0149] <Measurement Method>

[0150] (Methods for measuring the thickness of cured film)

[0151] The thickness of the release film was measured using a micrometer and set to 0 μm. Subsequently, the overlap between the release film and the adhesive film was measured, and the difference was taken as the thickness of the adhesive film. Nine measurements were taken for each sample, and the average (arithmetic mean) was taken as the thickness of that sample. The average thickness of five samples was calculated, and the average (arithmetic mean) was taken as the final thickness. Furthermore, no significant difference in thickness was found between the adhesive film and the cured film.

[0152] (Methods for measuring water absorption rate)

[0153] Samples with a thickness of less than 40 μm were bonded together using a hand roller at a stage temperature of 90°C to achieve a thickness of 40 μm or more. Samples cut into 50 mm × 50 mm pieces were dried at 180°C for 60 minutes, cooled in a desiccator, and their weight after drying was measured. Subsequently, they were immersed in distilled water, removed after 24 hours, and their weight was measured again. The weight after water absorption was calculated using the formula: (weight difference before and after water absorption / weight after drying) × 100. Five samples were measured, and their average (arithmetic mean) was used as the water absorption rate. Furthermore, water droplets adhering to the sample surface were wiped off immediately after removing the test piece from the distilled water. Detailed experimental procedures for this step can be found in JISK 7209:2000.

[0154] (Methods for measuring transmittance and reflectance)

[0155] A glass slide was placed on a heating plate heated to 90°C. A film-like adhesive was applied from above the slide using a hand roller. After peeling off the release film from one side of the adhesive film, the slide was cured by heating at 180°C for one hour in a dryer. Transmittance and total reflectance in the range of 400 nm to 1100 nm were measured from the surface of the cured film using a U-4100 testing machine (manufactured by HITACHI). The measured values ​​were the average (arithmetic mean) of all measurements within the 400 nm to 1100 nm range. Nine points were measured for each sample, and their arithmetic mean was used as the transmittance and reflectance of that sample. Measurements were performed on five samples, and their arithmetic mean was used.

[0156] (Methods for measuring adhesive strength)

[0157] Adhesion strength (Si: MPa): 260℃

[0158] First, using a manual laminator (trade name: FM-114, manufactured by Technovision), at a temperature of 90°C and a pressure of 0.3 MPa, the film-like adhesive with a release film obtained in each example and comparative example was bonded to one side of a virtual silicon wafer (8 inches in size, 350 μm in thickness). Then, after peeling the release film from the film-like adhesive, using the same manual laminator at room temperature and a pressure of 0.3 MPa, dicing tape (trade name: K-13, manufactured by Furukawa Electric Industries, Ltd.) and a dicing frame (trade name: DTF2-8-1H001, manufactured by DISCO) were bonded to the surface of the film-like adhesive on the opposite side of the virtual silicon wafer. Next, a cutting device (trade name: DFD-6340, manufactured by DISCO) equipped with dual-axis cutting blades (Z1: NBC-ZH2050 (27HEDD), manufactured by DISCO / Z2: NBC-ZH127F-SE (BC), manufactured by DISCO) was used to cut virtual chips of 2mm × 2mm size from the virtual silicon wafer side. At the same time, in order to serve as a base, a cutting tape (trade name: K-13, manufactured by Furukawa Electric Industries, Ltd.) and a cutting frame (trade name: DTF2-8-1H001, manufactured by DISCO) were bonded to the grinding surface of the virtual silicon wafer (8-inch size, 350μm thickness) using the same manual laminator at room temperature and pressure of 0.3MPa. Next, a 12mm × 12mm base is obtained by cutting from the virtual silicon wafer side using a cutting device (trade name: DFD-6340, manufactured by DISCO) equipped with dual-axis cutting blades (Z1: NBC-ZH2050 (27HEDD), manufactured by DISCO / Z2: NBC-ZH127F-SE (BC), manufactured by DISCO).

[0159] Next, the virtual chip with film-like adhesive is picked up from the cutting tape using a chip bonding machine (trade name: DB-800, manufactured by Hitachi High Technology Co., Ltd.). It is then thermo-bonded at 120°C, pressure of 0.1MPa (load 400gf), and time of 1.0 second to bond the film-like adhesive side of the virtual chip with film-like adhesive to the opposite side of the ground surface of the base (silicon wafer, 12mm square). The film-like adhesive is then heated at 180°C for one hour in a dryer to thermo-cure the film-like adhesive and form a cured film.

[0160] For virtual chips with cured films bonded to a substrate, the shear peel force (adhesive force) of the bonded chip relative to the leadframe substrate at 260°C was measured using a universal bonding strength tester (trade name: 4000PXY series, Nordson Advanced Technology Co., Ltd.). Ten samples were used, and their average value (arithmetic mean) was taken.

[0161] (Methods for measuring fit)

[0162] First, the film-like adhesive with release film obtained in each example and comparative example was bonded using a manual laminator (trade name: FM-114, manufactured by Technovision) at a temperature of 60°C and a pressure of 0.3 MPa, so that one side surface of the virtual silicon wafer (size 8 inches, thickness 100 μm) came into contact with the film-like adhesive.

[0163] The wafer lamination performance was evaluated according to the following evaluation criteria. In this test, the evaluation level "○" indicates the level required for practical applications.

[0164] - Evaluation Criteria -

[0165] ○: The film-like adhesive adheres tightly to the entire virtual silicon wafer.

[0166] ×: The film adhesive is not tightly attached to the virtual silicon wafer.

[0167] There may be parts that are not tightly attached.

[0168] (Measurement of melt viscosity before curing)

[0169] Squares measuring 5.0 cm x 5.0 cm were cut from the release film adhesives obtained in the various embodiments and comparative examples. The cut film adhesives were then laminated with the release film removed. The laminates were pressed onto a 90°C stage using a hand roller to obtain a test piece with a thickness of approximately 1.0 mm. For this test piece, the change in viscous resistance was measured using a rheometer (RS6000, manufactured by Haake) under conditions of a temperature range of 25–250°C and a heating rate of 5°C / min. Based on the obtained temperature-viscous resistance curve, the melt viscosity (Pa·s) of the film adhesive at 70°C before curing was calculated.

[0170] In addition, the values ​​in the rows of each component in Tables 1-4 represent the content (parts by mass) of the corresponding component.

[0171] [Table 1]

[0172]

[0173] [Table 2]

[0174]

[0175] [Table 3]

[0176]

[0177] (Note) In Examples 16 and 17, the colorants contained epoxy resin (refer to item ET6N109).

[0178] [Table 4]

[0179]

[0180] Examples 1-21 contain specific amounts of epoxy resin (A), epoxy resin curing agent (B), polymer component (C), inorganic filler (D), and colorant (E). When cured, these films exhibit low total light transmittance and total light reflectance, demonstrating excellent optical properties. Furthermore, they exhibit excellent high-temperature adhesion and film-like adhesive bonding. Additionally, they demonstrate low water absorption, exhibiting favorable characteristics.

[0181] In Comparative Examples 1 and 2, the amounts of epoxy resin and inorganic filler were both below the specified limits, and no colorant was present. Furthermore, the amount of curing agent was also below the specified value. As a result, extremely high values ​​were observed in both total light transmittance and total light reflectance. The water absorption rate was also high. In addition, the adhesion at 260°C was also low.

[0182] In Comparative Examples 3 and 4, the amounts of epoxy resin and inorganic filler were higher than specified. As a result, the adhesion of the film adhesive was poor.

[0183] Comparative Examples 5 and 6 do not contain inorganic fillers. As a result, their water absorption rates are high.

[0184] In Comparative Example 7, the amount of epoxy resin was lower than the specified amount. Furthermore, an acrylic resin other than phenylene oxide resin was used as the polymer component. The results showed that the adhesion of the film adhesive was poor. Additionally, the total light transmittance was slightly higher.

[0185] The amount of colorant in Comparative Example 8 was lower than the specified amount. As a result, the total reflectance value was higher.

[0186] Based on the above results, it can be seen that, according to the present invention, the transmission and reflection of light in the cured film after the film adhesive has been cured can be suppressed. In addition, it exhibits excellent adhesion in the film adhesive before curing, and exhibits low water absorption and high adhesion at high temperature in the cured film.

[0187] Explanation of reference numerals in the attached figures:

[0188] 1 Lens

[0189] 2 Image Sensor

[0190] 3 cured film

[0191] 10-layer lens

[0192] 11 Sidewalls

[0193] 12 Adhesive parts

Claims

1. A film-like adhesive comprising epoxy resin (A), epoxy resin curing agent (B), polymer component (C), inorganic filler (D), and colorant (E), wherein, The polymer component (C) includes phenoxy resin. Relative to 100 parts by weight of the polymer component (C), the inorganic filler material (D) is 70 to 720 parts by weight. Relative to 100 parts by weight of the polymer component (C), the epoxy resin (A) is 70 to 350 parts by weight. The amount of epoxy resin curing agent (B) is 1.4 parts by weight or more, relative to 100 parts by weight of epoxy resin (A). When the total amount of the epoxy resin (A) and the polymer component (C) is set to 100 parts by mass, the colorant (E) is 10 parts by mass or more.

2. The film adhesive according to claim 1, wherein, The light transmittance of the cured film after curing at 120℃~180℃ is less than 10% in the range of 400nm~1100nm when the thickness is 10μm~125μm.

3. The film adhesive according to claim 1, wherein, The cured film cured at 120℃~180℃ has a light reflectance of less than 7% in the range of 400nm~1100nm when the thickness is 10μm~125μm.

4. The film adhesive according to claim 1, wherein, The thickness is in the range of 5μm to 150μm.

5. The film adhesive according to claim 1, wherein, When heated from 25°C at a rate of 5°C / min, the melt viscosity at 70°C is in the range of 6,000~65,000 Pa·s.

6. The film adhesive according to claim 1, wherein, The colorant (E) contains carbon black.

7. The film adhesive according to claim 1, wherein, The phenoxy resin is a thermoplastic resin with a molecular weight of 10,000 to 100,000, obtained by reacting a bisphenol compound with a glycidyl group-containing compound.

8. The film adhesive according to claim 1, wherein, The film adhesive is used for bonding lenses used in stacked lenses.

9. A stacked lens, wherein, The film-like adhesive according to any one of claims 1 to 8 is used in the bonding of the lens, and the cured film of the film-like adhesive is assembled into the stacked lens in such a way that it is bonded at the bonding part.

10. A concentrated solution for a film-like adhesive, wherein, The solvent contains: Phenoxy resin (C'); Epoxy resin (A) is 70 to 350 parts by weight relative to 100 parts by weight of phenoxy resin (C'); The epoxy resin curing agent (B) is 1.4 parts by mass or more relative to 100 parts by mass of epoxy resin (A); Inorganic filler (D), comprising 70-720 parts by weight relative to 100 parts by weight of phenoxy resin (C'); and The colorant (E) is 10 parts by mass or more when the total amount of the epoxy resin (A) and the phenoxy resin (C') is 100 parts by mass.

Citation Information

Patent Citations

  • Pressure sensitive adhesive sheet

    JP2023112140A